Regulation of molecular subtypes of pancreatic cancer by TET2 and 5'hmC - Eyres, MMD (2019)
Genomic studies using mRNA datasets have uncovered two molecular subtypes within pancreatic ductal adenocarcinoma (PDAC) tumours with distinct gene programmes and clinical characteristics, raising the possibility of subtype specific therapeutic options. In each of these studies a similar aggressive subtype was identified that was characterized by a loss of endodermal differentiation markers such as GATA6 and PDX1, as well as poorer patient survival, referred to collectively as squamous. Despite the inherent heterogeneity in the molecular basis of PDAC, there is little genetic heterogeneity between different PDAC tumours, even when comparing metastasis to primary tumours. Conversely, there is widespread epigenetic reprogramming association with progression to more aggressive phenotypes, suggesting that aggressive molecular subtypes are likely to be epigenetically driven.